The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.17153/oguiibf.272723
|View full text |Cite
|
Sign up to set email alerts
|

Yükselen Piyasa Ekonomilerinde Finansal Gelişmenin Girişimcilik Üzerindeki Rolü

Abstract: Bu makale 17 yükselen piyasa ekonomisinde 2004-2009 dönemi için finansal gelişmenin girişimcilik üzerindeki rolünü panel veri tahmin metotlarını kullanarak incelemektedir. Bu amaçla, finansal gelişme göstergeleri, kurumsal faktörler ve ekonomik koşulların girişimcilik üzerine etkisi ampirik olarak araştırılacaktır. Değişkenler arasındaki bağlantıları belirlemek için, iki farklı finansal gelişme ölçütü ve üç kurumsal faktör analizlere dahil edilmiştir. Ampirik bulgular, finansal gelişme ile kişi başına gelirin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 88 publications
4
3
0
Order By: Relevance
“…Again, our argument was supported, as we found positive moderating effect of financial openness on this nexus. Our results confirm the findings of Kar and Ozsahin (2016) and Abubakar (2015) in this regard. In addition, we used GMM estimation to check the robustness of our results and found support for our earlier findings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Again, our argument was supported, as we found positive moderating effect of financial openness on this nexus. Our results confirm the findings of Kar and Ozsahin (2016) and Abubakar (2015) in this regard. In addition, we used GMM estimation to check the robustness of our results and found support for our earlier findings.…”
Section: Discussionsupporting
confidence: 92%
“…Abubakar (2015) mentioned the lack of financial openness as the main hindrance in entrepreneurial activities in Africa. Similar results were reported by Llussá (2009) in case of 41 developing and developed countries, Kar and Ozsahin (2016) in case of 17 emerging economies, Wujung and Fonchamnyo (2016) in case of Cameroon, Fan and Zhang (2017) in case of China and Bayar et al (2018) in case of 15 middle income and high income economies.…”
Section: Literature Review and Hypotheses Developmentsupporting
confidence: 74%
See 1 more Smart Citation
“…A well-functioning financial system provides new economic opportunities for entrepreneurs, but does it play a major role in increasing entrepreneur activity? The empirical studies exploring the interaction emphasized that financial development has a positive impact on entrepreneurial activity [43][44][45][46][47][48].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kar and Ozsahin [46] analyzed the interaction between financial development and entrepreneurship in 17 emerging market economies over the period [2004][2005][2006][2007][2008][2009], and revealed that financial development proxied by credit to the private sector positively affected the entrepreneurship.…”
Section: Literature Reviewmentioning
confidence: 99%